2022
DOI: 10.3390/membranes12040378
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biocompatibility Analysis of a Novel Barrier Membrane Based on Bovine Dermis-Derived Collagen for Guided Bone Regeneration (GBR)

Abstract: Collagen-based barrier membranes are nowadays the prevalent option for Guided Bone Regeneration (GBR) procedures. Xenogeneic collagen is highly biocompatible as it shares a similar structure to native human collagen, which prevents it from eliciting an exaggerated host immune response. Most commercially available collagen barrier membranes are porcine-derived, while bovine-derived alternatives are still rarely available. The aim of the present study was to investigate the tissue responses and the barrier funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Reactive tissue could penetrate the membrane through the interstices between the fragments and substantial vascularization occurred. This particular pattern of integration and degradation is not observed in porcine collagen membranes and has been defined by researchers as “secondary porosity” [ 219 , 220 ].…”
Section: Biological Mechanisms Of Collagen Membranementioning
confidence: 97%
See 1 more Smart Citation
“…Reactive tissue could penetrate the membrane through the interstices between the fragments and substantial vascularization occurred. This particular pattern of integration and degradation is not observed in porcine collagen membranes and has been defined by researchers as “secondary porosity” [ 219 , 220 ].…”
Section: Biological Mechanisms Of Collagen Membranementioning
confidence: 97%
“…Reactive tissue could penetrate the membrane through the interstices between the fragments and substantial vascularization occurred. This particular pattern of integration and degradation is not observed in porcine collagen membranes and has been defined by researchers as "secondary porosity" [219,220]. Barbeck et al evaluated two porcine dermal-derived collagen membranes (Mucoderm and Collprotect) and noted that although neither membrane showed successful transmembrane vascularization, the Mucoderm membrane containing the vascular backbone allowed for microvascular penetration associated with the inward growth of connective tissue [87].…”
Section: Biological Mechanisms Of Collagen Membranementioning
confidence: 99%
“…In China, two of the most extensively used non‐cross‐linked collagen membranes are Bio‐gide (BG), which is a porcine‐derived, non‐cross‐linked collagen membrane, and Heal‐all (HA), which is a bovine‐derived, non‐cross‐linked membrane made from the skin using decellularization. Experiments have revealed that bovine and porcine derived non‐cross‐linked collagen membranes degraded differently in vitro, and in vivo, 34,35 a detailed study of in vitro biophysical characters and in vivo host tissue responsive processes of HA and BG are hence needed as it might be instructive to their respective clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have revealed that bovine and porcine derived non-crosslinked collagen membranes degraded differently in vitro, and in vivo, 34,35 a detailed study of in vitro biophysical characters and in vivo host tissue responsive processes of HA and BG are hence needed as it might be instructive to their respective clinical applications.…”
mentioning
confidence: 99%
“…Then 100 mg of bioglass was implanted in the subcutaneous pocket under sterile conditions and the wound was stitched with nonabsorbable suture materials. At 10 or 30 days post implantation, animals were sacrificed using an overdose of the anesthesia to analyze both the early and late tissue responses to the biomaterials in accordance with previous publications (28,32). The biomaterials were extracted with their surrounding tissue and placed in formaldehyde solution for preservation for 24 Histological workup.…”
Section: Bioglass Characterization In Vitromentioning
confidence: 99%